AN INVESTIGATION ON THE SOCIO-ECONOMIC BENEFITS AND CHALLENGES FACED BY FISHERS AROUND RIVER DONGA TARABA STATE, NIGERIA - AMOS, J.T; JA’AFRU, A.; Filli, F.B. (Nigerian Journal of Fisheries, 2018)
The study was conducted from March 2018 to August 2019 to investigate the socio-economic and challenges faced by fishers around River Donga. Structured questionnaires were administered to 242 fishers and data was analyzed using SPSS Version 23. Fishers’ age group showed middle-aged had the highest value (66.12%) while old age was lowest (2.48%). Sex showed males had the highest (96.69%) while females were lowest (3.31%). Marital status showed married had highest (83.47%) while divorced were lowest (0.83%). Educational level revealed primary school leaver had highest (51.24%) while those with tertiary education were lowest (5.79%). Alternative livelihood highest was the animal and plant farming (62.81%) and trading was lowest (3.31%). Fishing experience highest was 21-30years (38.8%) while lowest ≥51 (1.65%). The most effective of fishing regulations was the ban on the use of poison (3.95) mean score while the lowest was restricted season and area (1.68). Profitability regression analysis was significant for age, marital status, educational background, market distribution, and gear depreciation (P<0.05). Gender, experience, and craft depreciation not significant (P>0.05). Challenges faced by fishers’ highest was gear and fish theft (31.34%) while seasonal/climate change was least (1.14%). There is a decline in performance, from the negligence of fishing communities with benefits accrue to them by the Government. Fishers show support in abiding by fishing regulations if properly implemented.